Analysis of Compliance, Competency and Motivation Factors on the Performance of Employees at Undaan Eye Hospital Surabaya - Wulyatie, Larashati; Sentot Imam Suprapto; Indasah (Universitas STRADA Indonesia, 2025)
A hospital is a complex service organization that requires human resources as workers to help the company's activities run smoothly. Good performance is influenced by employee competence, satisfaction and motivation. This type of research was given to 112 respondents. Based on the research results, there is a positive influence on performance from competency of 0.671, compliance of 0.167 and motivation of 0.079. The results of the coefficient of determination (R Square) of 0.790 show that the performance of Undaan Eye Hospital employees is influenced by fulfillment, competence and motivation by 79% while the remaining 21% is from other factors.